Efficacy of Azithromycin in Comparison with Metronidazole in the Treatment of Chronic Periodontitis - Jawna'a K Mammdoh (University of Mosul, College of Dentistry, 2011)
Aims: The aim of this study was to evaluate the clinical effects of systemic azithromycin as an adjunct to scaling and root planning (SRP) and compared it with metronidazole in the treatment of chronic periodontitis. Materials and Methods: Forty four patients with clinical diagnosis of chronic periodontitis underwent scaling and root planing were divided into three groups. The first group (n = 20) patients received azithromycin 500 mg once daily for 3 days plus SRP. The second group (n= 11) received metronidazole 500 mg 3 times daily for 7 days plus SRP. The third control group (n= 13) patient received SRP plus placebo treatment once daily for 3 days. Clinical measurement including gingival index, bleeding on probing and probing pocket depth were performed at the base line visit and 40 days after taking the treatment. Results: The results obtained at 40 days from the base line showed better significant improvement in all clinical parameters (p≤ 0.05) in the treated groups, except for bleeding on probing in control group were no significant improvement was reported. Azithromycin plus SRP give the greatest improvement in mean gingival index and bleeding on probing (p< 0.05) when compared with the control group but no significant differences were observed between metronidazole treated group and the control group. Conclusions: The adjunctive use of azithromycin with SRP has potential to improve periodontal health over SRP only and could be an interesting alternative to metronidazole from patients with chronic periodontitis